TRANSMUTATIONS OF PLOT AND CHARACTERS: A COMPARATIVE ANALYSIS OF THE ANIMATED FILM THE LION KING (1994) AND THE LIVE-ACTION THE LION KING (2019) - Wanda Andres Saputra; Asmanadia Izzatul Karimah; Zaidi, Abdullah (UIN Raden Mas Said Surakarta, 2023)
This study aims to reveal the existence of transmutations of the plot and characters in the film adaptation. This study uses theory (Stam, Robert 2000) to find transmutations of plot and characters and theory (Hutcheon, Linda 2012) for a comparative analysis of the film adaptation of the animated version of